Traditional Processing Method of Smoked Corbicula fluminea (Etak): Case of Etak Vendor in Kelantan, Malaysia. Issue 1 (December 2020) - Rak, Aweng Eh; Azizan, Ahamad Tarmizi; Yaacob, Mohd Rafi; Hamzah, Zulhazman; Syed Omar, Sharifah Aisyah; Zakaria, Mohd Nazri; Ismail, Mohamad; Wan Ibrahim, Wan Khairy; Mohamad Rani, Wan Siti Farizan; Zaki, Mohd Zaim; Mohammed, Arifullah
Abstract: Traditional knowledge is very synonymous with communities and tribes around the world, especially indigenous peoples or in Malaysia known as Orang Asli. This knowledge is borne out of the constraints faced by society in daily life and often passed down from generation to generation. All aspects of life in the community such as traditional medicines, pest and disease control, farming method, tools used in the preparation of soil and roads, methods of food preparation and so on are assisted by the traditional knowledge created by the community itself. Asian clams (Corbicula fluminea), locally known as "etak" in Kelantan dialect, Malaysia, has been consumed by the local community as a snack for a years. Smoked "etak" is prepared traditionally using freshly harvested "etak" from the river or natural habitat. Freshly harvested "etak" is then washed thoroughly and soak overnight to remove sand and dirt. Followed by, marinating with the previously prepared spices and soak for about 2 hours. The last process is to smoke the "etak" on the fire with medium heat. "Etaks" are placed on a platform made of bamboo with height of about one meter above the ground. Beneath it was lighted with firewood and before "etak" can be placed on a bamboo platform, it was necessary to make sure that the firewood is burned to the coals. This is to ensure that the "etak" shell is not opened as it is considered to be damaged and should not be eaten as a snack. "Etak" with shell open will dry and lose its juiciness and flavor. "Etak" should be stirred all the time when it is on a platform with medium heat fire. "Etak" is usually smoked for about 45 minutes and left to cool down before eating or selling. Based on an interview and observation conducted, it can be concluded that smoked "etak" which is prepared using traditional method is preferred by consumers, as it has a unique aroma and flavor. Hence, the current study aims to document this knowledge through informal conversational interview with "etak" smokers and consumers in Kelantan as well as observing the working mechanism of this method.